A bird's eye view: Sexual health adviser coordination of contact tracing for hepatitis B. (April 2021) - King, Sam; Murchie, Martin; Dalrymple, Jenny
An National Health Service sexual health adviser led service to facilitate management of new cases of hepatitis B from all settings across a large Scottish health board was initiated in 2012. Sexual health advisers contacted testing clinicians to support referral into appropriate services and facilitate identification, testing and vaccination of sexual partners, family and household contacts. A retrospective audit of contact tracing outcomes was conducted between September 2012 and December 2019. From a total of 1344 people diagnosed with hepatitis B, 2248 household and sexual contacts were identified. A documented outcome was established for 1741 (78%) of contacts, equalling 1.3 per index case. 257 (11%) of traced contacts were hepatitis B surface antigen positive, 162 (7%) had natural immunity and 1222 (54%) were vaccinated, either before or after contact tracing. This suggests a multi-agency approach to contact tracing for hepatitis B can achieve good outcomes. Further work is required to reduce the disproportionate burden of hepatitis B among ethnic minority subpopulations in Scotland.